Dynamical changes of seismic properties prior to, during, and after 2014–2015 Holuhraun Eruption, Iceland - Sudibyo, Maria R.P.; Eibl, Eva P. S.; Hainzl, Sebastian; Ohrnberger, Matthias (Copernicus Publications, 2024)
In volcanic eruption monitoring, it is urgent to promptly detect changes in the volcanic system during the crisis period. Ideally continuous, temporally high-resolution, multidisciplinary data is available for this. However, some volcanoes are only being monitored using a single discipline or a single seismic station. In this case, it makes sense to harvest information from the available limited data set with several different techniques. Changes in the seismic complexity could reveal the dynamic changes due to magma propagation. We tested the performance of Permutation Entropy (PE) and Phase Permutation Entropy (PPE), which are fast and robust quantification of time series complexity, to monitor the change in the eruption process of 2014–2015 Holuhraun in Iceland. We additionally calculated the instantaneous frequency (IF), which is commonly used to monitor the frequency changes in a non-stationary signal. We observed distinct changes in the temporal variation of PE, PPE, and IF, which are consistent with the changing state from quiescence to magma propagation and then to eruption. During the eruption, PE and PPE fit the lava discharge rate, showing their potential to forecast the duration of the eruption. Finally, we also assessed the influence of the atmospheric noise to be considered in eruption monitoring.